The history of nomadic animal husbandry research in Tuva (review) - Mongush, Saiana D.; Bondarenko, Olga V.; Biche-ool, Saiana Kh.; Kombu, Ailaana M. (The New Research of Tuva, 2024)
The article presents a historiographical review of research on nomadic animal husbandry in Tuva, spanning from the late 19th century to the present day. It includes a classification of studies, the identification of key scientific problems and research directions, as well as their evolution and transformation. The article examines the most significant works in two domains: historical-ethnographic and historical-economic. The origins of research date back to the early records of travelers and the first scholars of the region, which provided general information about livestock species, the characteristics of Tuvan livestock breeds, conditions of their maintenance, and more. These early accounts highlighted the adaptation of local livestock to environmental conditions, their resilience, adaptability, and endurance, as well as the disadvantages of traditional Tuvan grazing practices. During the Soviet period, research adopted a more systematic character. Historical studies began to diverge based on academic disciplines, incorporating approaches from both ethnography and economics. It is noted that the classic works of Tuvan studies on the traditional forms of nomadic livestock husbandry among Tuvans were published in the 1970s and continue to hold relevance and influence in contemporary Tuvan studies. Re-evaluations have been made regarding the policies and outcomes of sedentarization. The topic of lifestyle changes among Tuvan nomads and the organization of their traditional economies in the post-Soviet period has shifted into the realms of ethnographic, cultural, and anthropological research. These studies primarily document and analyze the results of transformational processes. The integration of economic research, particularly in the interdisciplinary field of historical economics, broadens our understanding of what occurred with nomadic livestock husbandry in Tuva during the 20th century, especially within the framework of socialist transformations and planned economies. Soviet economic science focused primarily on addressing state objectives for livestock husbandry as a sector of the socialist economy. The article emphasizes that post-Soviet domestic science has yet to fully abandon the legacy of Soviet perspectives and evaluative terminology in characterizing traditional forms of economy. In recent years, Tuvan economic science has shifted its focus to traditional forms of Tuvan economic activity, paying closer attention to the sociocultural factors shaping the livelihoods of the local population.
Keywords: animal husbandry; nomadism; Tuvans; traditional economy; Republic of Tuva; agriculture; livestock; historiographical review; Tuvan studies